2018
DOI: 10.4012/dmj.2017-233
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and color stability of dental flowable composites influenced by simulated toothbrushing

Abstract: This study evaluated surface gloss, roughness and color change of six current flowable composites after simulated toothbrushing, including four traditional flowable composites (i.e. GrandioSO Flow, Arabesk Flow, Kerr Revolution Formula 2 and Gradia Direct LoFlo), one self-adhering flowable composite (Kerr Vertise Flow) and one universal injectable composite (G-ænial Universal Flo). Forty-eight dimensionally standardized specimens (n=8/group) were made from six composites. Before and after 1 h toothbrushing sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 40 publications
3
49
0
1
Order By: Relevance
“…However, the GU values for CS3, ESP, and KZR were lower than 70 after testing. Previous studies reported that the optimal value for composites is greater than 70 (16,17). Therefore, materials with a value lower than 70 are regarded as aesthetically inferior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the GU values for CS3, ESP, and KZR were lower than 70 after testing. Previous studies reported that the optimal value for composites is greater than 70 (16,17). Therefore, materials with a value lower than 70 are regarded as aesthetically inferior.…”
Section: Discussionmentioning
confidence: 99%
“…Gloss and surface roughness were measured before and after the toothbrush abrasion test, in accordance with the method of Koizumi et al (18). The angle of reflection of the gloss meter was 60 degrees (16)(17)(18). In addition, a laser microscope (1LM21W, Lasertec Corp., Yokohama, Japan) was used to determine Sa, a measure of surface roughness.…”
Section: Surface Roughness and Gloss Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,[43][44][45][46][47][48] Later on, a different photo-initiator (monoacylphosphine oxide (Lucirin TPO)) system has been introduced that is designed to improve polymerization kinetics and reduce photo-yellowing effects. 45,[49][50][51][52][53] The use of Lucirin eliminated the amine group, thereby increasing color stability upon aging. 25,45,48,[54][55][56] IPS Empress Direct (Ivoclar Vivadent, Schaan, Liechtenstein), a resin-based material, was introduced to the market.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, limited study has specifically investigated the ability of IPS Empress resin composite to match the color and optical properties of teeth. 12,52…”
Section: Introductionmentioning
confidence: 99%